Effects of a Garlic Active Based Growth Promoter on Growth Performance and Specific Pathogenic Intestinal Microbial Counts of Broiler Chicks - Kumar, Shiva; Sharadamma, K.C.; Radhakrishna, P.M. (International Journal of Poultry Science, 2010)
The present study was conducted to determine whether dietary supplementation of a natural non-antibiotic garlic active based growth promoter i.e. G-PRO naturo would be used as a natural alternative to antibiotics growth promoters in broiler diets. Three hundred sixty, 1-day-old straight run broiler chicks (Cobb 400) were randomly divided into 3 treatment groups of 20 birds each with 6 replicates. The groups were 1) Negative control (basal diet), 2) G-PRO naturo 250 ppm (+ basal diet) 3) Positive Control (basal diet + Virginamycin) 500 ppm. The basal diets (starter/grower: 0-21 d, finisher 22-42 d) were based on maize and soybean meal. Each group was fed ad libitum with its own diets for a period of 42 days. Light was provided 24 h each day throughout. Water was always available. The body weight gains of birds were measured individually and feed consumption and feed conversion efficiency (g feed: g weight) were calculated weekly. At the end of the experiment all birds were sacrificed to determine intestinal microbial count. The results obtained in the experiment showed that the garlic based additive supplementation affected some performance parameters significantly (p